Analysis of Tourist Satisfaction to Tourist Attraction Quality in Kediri Regency, East Java - Cyntha Tendean (Program Pascasarjana, 2017)
This research aims to determine tourist satisfaction towards service quality which involves attraction, accommodation, accessibility, facility, information, advertisement, and utilities availability in Kediri Regency Tourism Attraction. Importance Performance Analysis (IPA) research method was utilized to determine tourist response regarding tourism attributes. The attributes are mapped according to importance and performance level. Then the attributes are mapped according to its respective quadrant, thus it could be exhibited which variables requiring improvement or further attention. Based on IPA diagram plotting result, Temple of Surowono and Temple of Tegowangi possesses 8 out of 29 attributes, while Gereja Tua Puh Sarang possesses 1 out of 29 attributes requiring service improvement. Attributes in Quadrant I are included in primary priority which is important for cultural tourism. This attributes requires more attention in order to increase tourist satisfaction.Keywords: Cultural Tourism Attraction, Customer Satisfaction, Quality.